38.0k views
3 votes
(8x-11)-(15-x)=1 dont know where to start with it​

User Prasoon
by
5.3k points

2 Answers

4 votes

Answer: x=3

Explanation:Step 1: Simplify both sides of the equation.

(8x-11)-(15-x)=1

(8x-11)+-1(15-x)=1 (distribute the negative sign)

8x+-11+-15+x=1

8x+x+(-15+-11)=1 (combine like terms)

9x+-26=1

Step 2: Add 26 to both sides

9x-26+26=1+26

9x=27

Step 3: Divide both sides by 9.

9x/9=27/9

x=3

User Mohit Verma
by
5.9k points
4 votes

Answer:

x = 3

Explanation:

First open the brackets. While opening brackets, you've to be careful about signs. So when you open bracket of (15-x), there's negative sign in front of it, so it makes the signs inside the brackets to change. Then you solve the it.

(8x-11)-(15-x)=1 dont know where to start with it​-example-1
User Maksym Kozlenko
by
6.1k points